2021
DOI: 10.1177/2331216521997610
|View full text |Cite
|
Sign up to set email alerts
|

Can Dual Compression Offer Better Mandarin Speech Intelligibility and Sound Quality Than Fast-Acting Compression?

Abstract: The aim of this study was to evaluate the efficacy of dual compression for Mandarin-speaking hearing aid users. Dual compression combines fast and slow compressors operating simultaneously across all frequency channels. The study participants were 31 hearing aid users with symmetrical moderate-to-severe hearing loss, with a mean age of 67 years. A new pair of 20-channel behind-the-ear hearing aids (i.e., Phonak Bolero B90-P) was used during the testing. The results revealed a significant improvement in speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Therefore, the finding is consistent with the ELU model: context is assumed to aid listeners to unload WM because it could facilitate prediction and thus, no additional explicit processing is necessary for sentence recognition in noise [ 11 ]. This finding is also consistent with our previous study [ 26 ] conducted with Mandarin-speaking adults with hearing aids, where the Mandarin version of HINT and the same lexical tone manipulation methods were used; results showed that WM did not significantly affect sentence recognition in SSN among this population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the finding is consistent with the ELU model: context is assumed to aid listeners to unload WM because it could facilitate prediction and thus, no additional explicit processing is necessary for sentence recognition in noise [ 11 ]. This finding is also consistent with our previous study [ 26 ] conducted with Mandarin-speaking adults with hearing aids, where the Mandarin version of HINT and the same lexical tone manipulation methods were used; results showed that WM did not significantly affect sentence recognition in SSN among this population.…”
Section: Discussionsupporting
confidence: 92%
“…Although the FT 60% condition provided more lexical tone information than the FT 100% condition, the former may have deployed more WM capacity than the latter. FT 100% sentences made it easier to “track” the target stream, thereby making sentence recognition less cognitively demanding, especially for attention and WM [ 26 ]. This finding may explain why some novel cochlear implant (CI) speech processing strategies designed explicitly to incorporate more tonal information have failed to contribute significantly to sentence recognition in noise compared to present CI speech processing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the preceding discussion largely addressed only objective benefit, i.e., aided speech intelligibility, in various situations, but not the perceptions of users that will affect outcomes, not least in mediating compliance with treatment. A number of studies show that users generally prefer SAC in noisy, or all, situations ( 107 , 141 , 184 , 193 ) or that different individuals have different preferences, with a greater average preference towards SAC ( 180 ).…”
Section: Implications For Hearing Aid Fittingmentioning
confidence: 99%
“…HA features (e.g., compression parameters, noise reduction, and directional microphone) were not included in the analysis. As some HA features (e.g., compression parameters) have been found to be significantly related to speech perception in noise ( Stone et al, 2009b ; Chen et al, 2021 ), it is possible that these HA features might have mediated the relationship between cognitive function and sentence perception in noise in the HA group.…”
Section: Discussionmentioning
confidence: 99%